The magic mirror: a novel intraoperative monitoring method for parathyroid glands - Yuan, Yue; Li, Xiao; Bao, Xin; Huangfu, Mingmei; Zhang, Hong (Frontiers in Endocrinology, 2023)
The accurate detection of parathyroid glands (PGs) during operation is of great significance in thyroidectomy and parathyroidectomy, which means the protection the function of normal PGs to prevent postoperative hypoparathyroidism and thorough removal of parathyroid lesions. Existing conventional imaging techniques have certain limitations in real-time exploration of PGs. In recent years, a new, real-time and non-invasive imaging system—near-infrared autofluorescence (NIRAF) imaging system has been developed to detect PGs. Many studies have confirmed that this system has a high parathyroid recognition rate and can reduce the occurrence of transient hypoparathyroidism after surgery. The NIRAF imaging system, like a magic mirror, can monitor the PGs during surgery in real time, becoming a good helper for surgeries. Besides, the NIRAF imaging system can evaluate the blood supply of PGs by indocyanine green (ICG) to guide surgical strategy. NIRAF imaging system and ICG complement each other to protect normal parathyroid function and reduce the postoperative complications. This article reviews the effectiveness of NIRAF imaging system in thyroidectomies and parathyroidectomies, and briefly discusses some existing problems and prospects for the future.[]